Species diversity, taxonomy and distribution of Chondrichthyes in the Mediterranean and Black Sea. Issue 1 (1st January 2020) - Serena, F.; Abella, A. J.; Bargnesi, F.; Barone, M.; Colloca, F.; Ferretti, F.; Fiorentino, F.; Jenrette, J.; Moro, S.
Abstract: Species diversity assessments are an important step to evaluate the conservation status of a community, both in marine and terrestrial ecosystems. These assessments are pivotal if related to both, the constant increase of human pressure on ecosystems and the anthropogenic climate change occurring nowadays. Sharks and rays are globally threatened, and the situation is particularly alarming in the Mediterranean Sea where more than 50% of species are listed at risk of extinction by the International Union for Conservation of Nature (IUCN). In this paper, we revise and discuss the chondrichthyan species richness of the Mediterranean and the Black Sea. Through an accurate review of published taxonomic studies, historical data on species occurrence, analyses of scientific survey data and biodiversity databases and other scientific papers, we produced a revised list of species whose presence in the Mediterranean Sea is confirmed or highly probable and discussed on current taxonomic and occurrence disputes on the species that are instead rarer or claimed to be locally extinct. We listed a total of 88 species, representing 30 families and 48 genera that are currently present in the Mediterranean and the Black Sea. This number includes 48 shark species, 38 batoids, and 2 chimaeras. The review represents a reference for future conservation assessments of cartilaginous fish in the region and a guide for decision-makers when promoting the sustainable exploitation of fisheries resource within an ecosystem-based framework. This paper can help to set a baseline of the Mediterranean species and thus resolve some uncertainties regarding their conservation status, explaining the reasons for their prolonged absence in the reports. Indeed, failure to record over time may not be due to grubbing up, but because after careful review this species was not really part of the Mediterranean fauna.